Harvesting energy from the dynamic deformation of an aircraft wing under gust loading - Pozzi, Michele; Guo, Shijun J.; Zhu, Meiling (Cranfield University, 2012)
Weight reduction and maintenance simplification are high in the agenda of companies and researchers active in the aerospace sector. Energy harvesters are being investigated because they enable the installation of wireless sensor nodes, providing structural health monitoring of the aircraft without additional cabling. This paper presents both a weight-optimized composite wing structure and a piezoelectric harvester for the conversion of mechanical strain energy into electrical energy. Finite elements modelling was used for the minimum- weight optimisation within a multi-constraints framework (strength, damage tolerance, flutter speed and gust response). The resulting structure is 29% more compliant than the original one, but is also 45% lighter. A strain map was elaborated, which details the distribution of strain on the wing skin in response to gust loading, indicating the optimal locations for the harvesters. To assess the potential for energy generation, a piezoelectric harvester fixed to a portion of the wing was modelled with a multi-physics finite elements model developed in ANSYS. The time-domain waveforms of the strain expected when the aircraft encounters a gust (gust frequencies of 1, 2, 5 and 10 Hz were considered) are fed into the model. The effects of harvester thickness and size, as well as adhesive thickness, were investigated. Energy generation exceeding 10 J/m2in the first few second from the beginning of the gust is predicted for 100μ-thick harvesters. The high energy density, low profile and weight of the piezoelectric film are greatly advantageous for the envisaged application